Вы находитесь на странице: 1из 5

# . .

http://www.mathnet.spb.ru

. ()
(), .
. :
1. b a x = b .
2. b a x = b ,
a b :
a x = b x = log a b .
3. b :

0 < a < 1,

## a x > b x < log a b a x < b x > log a b .

4. b a x > b
, a x < b .
5. .

10. .
0, 2 x + 0,5
1.
= 5 0, 04 x .
5
, 5:
0, 2 x + 0,5
5 ( x + 0,5)
= 5 0, 04 x
= 51 52 x 5 x 1 = 51 2 x x 1 = 1 2 x x = 2 .
0,5
5
5
x

1
2. 0,125 2 0, 0625 x .
2

, , ,
x

1
1 1
x
2
0,125 2 0, 0625 2
2
2 8
x

4 x

1 1 1 2 1

2 2 2
2
1
7
x + 3 4x x .
1
2
10
<1

1

2

x +3

1

16

1

2

1
4 x
2

1
:
2

3. : (2 3) x = (2 + 3) x .
,
:
2
2
x = 0;
(2 3) x = (2 + 3) x (2 3) x = (2 3) x x 2 = x
x = 1.
20. .
a f(x) = b f(x) ,
, .
: 52 x 4 = 492 x .
1
52 x 4 = 492 x 52 x 4 = 7 4 2 x 52 x 4 =
7
1

2 x 4

352 x 4 = 1 2 x 4 = 0 x = 2.

30. .
()
, ()
. , ab = a c ab c .
1. 2 x +1 + 2 x 1 + 2 x = 28 .

2 x +1 + 2 x 1 2 x = 28 2 x 1 (2 x +1( x 1) + 2 x 1( x 1) 2 x ( x 1) ) = 28
28
28
28
2 x 1 (22 + 1 2) = 28 2 x 3 = 28 2 x 1 =
x 1 = log 2
x = log 2
+ 1.
3
3
3
1
1
2. : 3 4 x + 9 x + 2 6 4 x +1 9 x +1 .
3
2
,
:
1
1
1
1
3 4 x + 9 x + 2 6 4 x +1 9 x +1 3 4 x 6 4 x +1 9 x + 2 9 x +1
3
2
3
2
x

1
63
63
1
4
(3 6 4)4 x 92 + 9 9 x 21 4 x 9 x

2
2
42
3
9
x

63
4
2
=

42
9
3

2x

2

3

1
2 x 1 x .
2 / 3 <1
2

40. .
1. 25 x 6 5 x + 5 = 0 .
5 x = t .
t = 1;
t 2 6t + 5 = 0
t = 5.

5 x = 1
x = 0;

x
x = 1.
5 = 5
2. 125 x + 20 x = 2 3 x+1 .
x

125 20
125 x + 20 x = 23 x+1 125 x + 20 x = 2 8 x
+ =2
8 8
5

2

3x

5
+ 2=0.
2

5
= t .
2
: t 3 + t 2 = 0 (t 1)(t 2 + t + 2) = 0 t = 1 .
x

5
= 1 x = 0 .
2
3. (5 + 2 6) x + ( 3 + 2) x > 12 .

( 3 + 2) x = t .
t > 3;
.
t 2 + t 12 > 0
t < 4.
( 3 + 2) x > 3

x > log
( 3 + 2) x < 4 . 3 + 2 > 1

3+ 2

3.

50. .
1. 2 81 x+1 36 x +1 3 16 x+1 = 0 .
2 81x+1 36 x +1 3 16 x+1 = 0 2 81x+1 9 x +1 4 x +1 3 16 x+1 = 0
9 x +1 3
=

x+1
x +1
x+1
x +1
2
4
81
36
81
9

2

3= 0 2

3=0

x +1
16
16
16
4
9

= 1, .
4

1
1
x= .
2
2

x +1 =
1
: .
2

2. 3 2 x 2 3 x
2

32x 2 3 x
3x
x+ 6
3

+ x +6

+ x +6

+ 3 2 x+12 > 0 .

## + 3 2 x+12 > 0 (3 x ) 2 2 3 x 3x + 6 + (3 x+ 6 ) 2 > 0

2

3x
2
2
2
2 x+ 6 + 1 > 0 (3 x x 6 ) 2 2 3 x x 6 + 1 > 0 3 x x 6 1

x 3
.
x2 x 6 0
x 2
: (; + ) \ {2; 3} .
2

60. .
5 x +1 + 3x
1. x
=1.
3 5x
3x
( 2 30):
x
5 x
5

5
1

+
x
9;

5 x +1 + 3x
4
4
3
3
5

1
1
=

= x = log 5 .

x+2
x
x
x
x
3
3
3
5
3
5
5
5
3
9
5
1
9

+
=

3
3
3

4

: log 5 .
3 3
1
1
2. x
x+1
.
3 + 5 3 1
3 x = t .
t < 5
t 3
1
1
1
1

0
0 1

<t 3
t + 5 3t 1
t + 5 3t 1
(t + 5)(3t 1)
3
x
3 < 5

3x > 31
x > 1
1

3x >
x
1

3
x 1
3 3
x
3 3

: (1; 1] .

70. .

. , f ( x) g ( x) = 0 , -
, .
, .
2

x 2 3

1. : x (9 x 3 3
, :

(9

x 2 3

x 2 3

) = 32

x 2 3 +1

x 2 3 0

x 0
6)( x 3) = 0
x 2 3 3
9

x = 3

x 2 3

x 2 3 +1

+ 6 x 18 .

x 3

x = 9
x 2 3

=3
6 = 0 3
x 2 3
= 2 .
3

x 3

x = 9
.
x = 9

x = 2
2
x 3 = 1
2. 6 x 8 3x 9 2 x + 72 0 .

x 3;
, (2 x 8)(3x 9) 0
x 2.
80. ( A( x) )

f ( x)

= ( A( x) )

g ( x)

( A( x) )
e f ( x )ln A( x ) ,
, A( x) (
).
:
A = 1;

( A( x) ) f ( x) = ( A( x) ) g ( x ) ...
f = g.
f ( x)

: ( x 2 + x 57) 3 x

( x 2 + x 57) 3 x

+3

+3

= ( x 2 + x 57) 10 x

= ( x 2 + x 57) 10 x

1 + 233
x 2 + x 57 > 0
;
x =

2
x 2 + x 57 = 1

1 233
2
.
x =
3
3
10
x
x
+
=

90. ( A( x) )
( A( x) )
.
, A( x) > 0 , :
f ( x)

g ( x)

A =1
A > 1, f ( x) g ( x)
( A( x) ) ( A( x) ) .
..
A < 1, f ( x) g ( x)
,
, , .
f ( x)

( x 2) x

( x 2)

x2 x

g ( x)

( x 2)12 .

12

( x 2)

x 2 =1

2 < x 3;
x 2 > 1, x 2 x 12

x 4.
0 < x 2 < 1, x 2 x 12

: (2 , 3] [ 4 , + )
4

, :
1.
2.
3.
4.
5.

0,125 64
x 4

3x 2

x+6
x

4x

x +2

x +2

0, 2

1
( x +1)
2

2x x+2

2x 2

x +1

16

x +12
x +1

1
( x + 7)
2

2 x x 1
2

+ 2 < 52

x 2
x 4

= 125 0, 04
3 x 1

>5

2 x 2 x +1

2 x 2 x 1

+3

x2

6 9 x 13 6 x + 6 4 x > 0

9.

22 x

+3x +5

10. (1 x) x

2x

+2x+4

2x+ 4 = 0

(1 x) 4 x 4

## 11. x2 22 x + 9( x + 2) 2x + 8x2 = ( x + 2) 22 x + 9x2 2x + 8x + 16

12.

x
+2
62

8.

3 52 + x
6 5 x 1 + 1

4 54 x
8 51 x + 3

6.
7.

+ 30 0
x
(11 + 6 2) + 2 (3 + 2) x 8 < 0

13. 52 x + 3 + 2 32 2 x 6 =

8
6.

5 x 1 + 5 0,2 x 2 = 26
64 x = 2 27 x 36 x

14. 3 2 x +1 = 3 x +1 + 1 6 3 x + 3 2( x +1)

7.

5 + 24 + 5 24 = 10

15. 33 x

27
3x

8 152 2 x + 14 32 2 x 22
4 52 2 x + 7

9 3x x1 = 8
3